Perkahwinan remaja: satu kajian di Kuching, Sarawak - Nor Jana Saim; Suini anak Lejem; Fatimah Abdullah; Noremy Md Akhir (Penerbit Universiti Kebangsaan Malaysia, 2018)
Commonly, teenage marriage affects schooling and being gainfully employed to support the family in later life. Most studies focused on the effects of marriage at the young age. However, less research is focusing on the experience of marriage from the perspective of the teenagers who get married at the teen age. This article aims to answer the following questions: (1) what are the experiences of teenage marriages, and (2) what are their views on teenage marriage. The article is based on semi-structured interviews with seven girls recruited by snowball technique, aged 15 to 23 years, married and living in Kuching, Sarawak. Data were analyzed by thematic analysis. Seven themes emerged on marriage experiences: being independent, nourishing patience, maintaining social boundaries, developing responsible behaviour, being inspired, staying positive and doubting their ability as a husband or wife. Moreover, four main themes described informants' views on teenage marriage: to avoid immorality, immaturity, making decisions wisely and accountability. It can be concluded that a person who gets married at the teen age is in need of help from various parties, especially parents and friends as well as community not to be stigmatized for being married at the teen age.